Primary ovarian neuroendocrine tumour arising in a benign mature cystic teratoma: a case report and literature review. Issue 2 (2nd July 2020) - Wadee, Reubina; Beavon, Ian; Smith, Trudy; Mbodi, Langanani
Abstract: Primary ovarian neuroendocrine tumours are very uncommon tumours. Herein, we describe a case of 27-year-old female who presented with abdominal pain and an ovarian mass, for which she underwent a right salpingo-oophorectomy. Histopathological evaluation confirmed a right-sided primary ovarian neuroendocrine tumour occurring in a benign mature cystic teratoma. The patient has not undergone any additional therapy and is currently well. This case illustrates the need for thorough clinicopathological correlation together with adequate sampling to ensure accurate diagnosis and timeous management of the patient.